Debates in the Digital Humanities 2019 - Klein, Lauren F.; Gold, Matthew K. (Book collections on Project MUSE., 2019)
Contending with recent developments like the shocking 2016 U.S. Presidential election, the radical transformation of the social web, and passionate debates about the future of data in higher education, Debates in the Digital Humanities 2019 brings together a broad array of important, thought-provoking perspectives on the field's many sides. With a wide range of subjects including gender-based assumptions made by algorithms, the place of the digital humanities within art history, data-based methods for exhuming forgotten histories, video games, three-dimensional printing, and decolonial work, this book assembles a who's who of the field in more than thirty impactful essays.